Advances in Business Entrepreneurship for Driving International Financial Technology Platform Expansion - Comfort Iyabode Lawal; Oluwasanmi Segun Adanigbo; Florence Sophia Ezeh; Solomon Christopher Friday; Unomah Success Ugbaja (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This paper explores the critical role of business entrepreneurship in driving the international expansion of Financial Technology (FinTech) platforms, highlighting the innovative strategies and business models that enable these companies to scale globally. The study examines entrepreneurial approaches to the development of FinTech services, emphasizing the adoption of cutting-edge technologies such as artificial intelligence, blockchain, and mobile platforms to cater to underserved populations. The paper analyzes key trends and challenges in emerging markets and underscores the significant impact of digital transformation and strategic partnerships on FinTech growth. Additionally, it discusses the regulatory barriers and compliance challenges that entrepreneurs face when expanding across borders, and how they can leverage global opportunities through adaptable business models. Through case studies and industry insights, the paper presents recommendations for entrepreneurs and policymakers to foster sustainable growth in international FinTech markets. This research contributes to understanding the evolving dynamics of the global FinTech industry and provides practical strategies for overcoming obstacles in global expansion.